Strategi Peningkatan Kinerja Karyawan Melalui Budaya Organisasi Dan Motivasi Kerja PT Zat Store: Strategi Peningkatan Kinerja Karyawan Melalui Budaya Organisasi Dan Motivasi Kerja PT Zat Store - Aqsa, Arsyid Fadillah; Afrizal, Muhammad; Wahjono, Sentot Imam (CV ODIS, 2025)
This study aims to analyze the influence of organizational culture and work motivation on employee performance. Using quantitative descriptive research methods, the study was conducted on 150 employees of PT Zat Store. Data collection was carried out through questionnaires and in-depth interviews. The results of the study indicate that organizational culture and work motivation significantly affect employee performance with a contribution of 67.5%. The implications of the study indicate the importance of developing a positive organizational culture and increasing work motivation to achieve optimal performance.